Detection of peanut (Arachis hypogaea) allergen by Real-time PCR method with internal amplification control. (1st May 2015) - Zhang, Wen-Ju; Cai, Qin; Guan, Xiao; Chen, Qin
Highlights: We establish a PCR method with IAC for detecting peanut in foods. We optimise the IAC concentration and make the limit of detection not influenced. The method can indicate the "false-negative phenomenon" in the experiment. The method can be applied into universal detection of food allergens. Abstract: Specific primer sets were designed based on the DNA sequence of Ara h 1, one of the major peanut ( Arachis hypogaea ) allergens, and a competitive internal amplification control (IAC) was designed by compound primer technology. By choosing 314 copies/PCR as the IAC dosage, a Real-time PCR method with IAC was established for detecting peanut allergen Ara h 1 DNA. The method showed high specificity with a detection limit of 0.005% peanut. A series of commercial food products with/without peanut components were tested. Among these products, the peanut allergen Ara h 1 DNA could be detected in 12 products labelled containing peanut ingredients, in two without a declaration of peanut and one labelled that was produced in a facility that produced peanut-containing foods. This indicates that the method is highly sensitive for the detection of peanut ingredients in foods.